Efektivitas Pembelajaran dengan Menggunakan Model Kamus Kata Penggolong Bahasa Mandarin Berbasis Nomina Alfabetis dalam Bahasa Indonesia - Imelda Imelda (Universitas Cokroaminoto Palopo, 2021)
Since the annulment of Presidential Instruction No. 14/1967, which prohibits the celebration of Chinese New Year and Chinese culture in Indonesia, there has been a gradual increase in Indonesian interest in Chinese culture, including learning Mandarin. And with the increasingly tight trade relations between China and Indonesia, the need for human resources who can communicate well, especially oral communication, increases. Mandarin learners in Indonesia are not limited to those who came from Chinese ethnic, but also come from non-Chinese ethnicities. The need for literacy materials for learning Mandarin is getting higher, this is needed to help the process of learning Mandarin language. This research used quantitative research methods with questionnaire data collection techniques. Respondents of this study were undergraduate students of Chinese Literature at Maranatha Christian University Bandung, class of 2019/2020. This study aims to determine the effectiveness of learning Chinese noun classifier words by using a Chinese noun classifier dictionary model based on alphabetical nouns in Indonesian.